ANTIPLATELET AGGREGATION ASSAY OF HOMOGENATE OF EUTYPHOEUS GAMMIEI- A NATIVE EARTHWORM OF TRIPURA, NORTH-EAST, INDIA: Pharmaceutical Science-Novel drug delivery System - DEBNATH MADHUSUDAN; DR. SHRIMATI DHARMAPAL SHETTY; SIL SAMIR KUMAR (International Journal of Life Science and Pharma Research, 2022)
For several years earthworms have been widely used in china, Japan, Indonesia, and the Far East to treat various chronic diseases. Intensive exploration has been made to reveal the use of earthworm as anti microbial anti inflammatory, anti pyretic and anti-cancer agents. Earthworm contains many compounds with potential medicinal properties and have been administered to treat inflammatory, hematological oxidative & nerve disease. It has been reported that medicinal activities of earthworm may vary depending on the species & living environment of that organism Cellular metabolism plays a vital role in the homeostasis of the bodyof any living organism. This metabolism is disturbed in conditions like thrombus that inhibits the blood supply to the body tissues leading to ischemia and finally necrosis of the cells. Hence, there is an urgent need for research in the field of antiplatelet and thrombolytic agents in order to prevent and cure thrombus thatleads to pathological conditions like Myocardial Infarction (MI), Hemiplegia and the like. It is essential to search for mineral medicines of similar nature which aid in a speedy recovery and are considered to be cost effective with a longer shelf life. The extract of Eutyphoeusgammiei (E.E.G) is used as a drug.As found in the literature, it is also used in cardiac ailments predominantly Angina and Mi for which thrombus is the reason behind the pathological condition. In this study, the extract of Eutyphoeusgammiei was evaluated for its in vitro antiplatelet aggregation and thrombolytic activity which proved effective at the dose of 65μl and 100μl respectively. Therefore, it can be concluded that Eutyphoeusgammiei (E.E.G) extract is an effective drug in the treatment of Cardiovascular diseases and Cerebrovascular accidents.